2001
DOI: 10.1021/ma001346x
|View full text |Cite
|
Sign up to set email alerts
|

Soft Interaction between Dissolved Flexible Dendrimers:  Theory and Experiment

Abstract: Using small-angle neutron scattering and liquid integral equation theory, we relate the structure factor of flexible dendrimers of fourth generation to their average shape. The shape is measured as a radial density profile of monomers belonging to a single dendrimer. From that, we derive an effective interaction of Gaussian form between pairs of dendrimers and compute the structure factor using the hypernetted chain approximation. Excellent agreement with the corresponding experimental results is obtained, wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 33 publications
8
119
0
3
Order By: Relevance
“…Both star polymers and flexible dendrimers fall into this fuzzy category, yet they may be highly aspherical. Likos et al [66] have also shown that stars and flexible dendrimers have the same kind of soft pair potentials. We thus expect such considerations of interfacial-area minimization to become highly relevant in the upcoming study of soft quasicrystals.…”
Section: Free-energy Functionals and Stability Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…Both star polymers and flexible dendrimers fall into this fuzzy category, yet they may be highly aspherical. Likos et al [66] have also shown that stars and flexible dendrimers have the same kind of soft pair potentials. We thus expect such considerations of interfacial-area minimization to become highly relevant in the upcoming study of soft quasicrystals.…”
Section: Free-energy Functionals and Stability Analysismentioning
confidence: 94%
“…Block copolymers, like homopolymers, can be linear or branched. Two branched architectures which can be well controlled, and thus have been drawing considerable attention recently, are star polymers [52][53][54][55][56][57][58][59][60][61][62], where the chains are joined in one point, and dendrimers [60,[63][64][65][66], having a tree-like structure.…”
Section: Quasicrystals-terminology and General Frameworkmentioning
confidence: 99%
“…Dendrimers. By employing a simple, mean-field theory based on the measured monomer density profiles of fourth-generation dendrimers, a Gaussian function of the form (2) has been shown to accurately describe the effective interaction between the centres of mass of these dendrimers [19,20]. The prefactor ε has in this case a higher value then for linear polymers, ε ∼ = 10 k B T .…”
Section: Effective Interactions Between Polymeric Macromoleculesmentioning
confidence: 99%
“…Before discussing the ramifications of these properties on the thermodynamics of the star polymer fluid, we point out that recently quite a bit of attention has been focussed on a related but distinct class of fluids, namely the ones whose constituent particles interact by means of positive-definite, purely repulsive potentials that do not diverge at the origin [104][105][106][107][108][109][110]. It was shown that for such systems, a 'meanfield limit' is satisfied [109]: at sufficiently high densities for all temperatures and at sufficiently high temperatures for all densities, the direct correlation function c(r) of the fluid [71] is approximated extremely well by its large-r asymptotic behavior, c(r) ∼ −βv(r) at all r. Hence, for bounded potentials and under the condition of high densities and/or temperatures, we can write at all separations and for all densities:…”
Section: The Mean-field Character Of the Star Polymer Fluidmentioning
confidence: 99%